What is the impact of mother’s bed incline on episodes of decreased oxygen saturation in healthy newborns in skin-to-skin contact after delivery: Study protocol for a randomized controlled trial - Jesús Rodríguez López; Nadia Raquel García Lara; María López Maestro; Javier De la Cruz Bértolo; José Carlos Martínez Ávila; Máximo Vento; Ana Parra Llorca; Isabel Izquierdo Macián; Adelina Pellicer; Natalia Marín Huarte; Izaskun Asla Elorriaga; Lourdes Román Echevarría; et al. (Trials, 2019)
Abstract Background Early mother–child skin-to-skin contact (SSC) in the first 2 h postpartum is highly beneficial for both mother and child. However, cases have been reported of newborns who have experienced apparently life-threatening events (ALTEs) or sudden death during this procedure. The causes of these events are unknown. Newborn’s prone position could influence the onset of these events but there is very little evidence to support any recommendation. We hypothesize that newborns’ breathing obstruction episodes increase as mothers lie more horizontally. The main objective of this study is to compare the occurrence of desaturation and bradycardia episodes as a function of mother’s bed incline. The study is designed as a randomized, controlled, assessor blind, multicenter, superiority trial with two parallel groups and 1:1 allocation ratio. Methods The study participants will be full-term healthy mother–newborn dyads from ten hospitals in Spain. Participants will be randomly assigned to one of two study arms defined by mother’s bed inclination (45° or 15°). The planned sample size is 5866. Centralized permuted blocks randomization and assessor blinding will be implemented. The newborns will be monitored remotely with pulse oximetry, from 10 min to 2 h after delivery. We established SO2 and heart rate (HR) limit alarms, as well as an action protocol in the event of alarm activation. The primary outcome is the number of healthy newborns who undergo episodes of SO2 ≤ 90%. Secondary outcomes are the mean SO2 level, the number of newborns who experience episodes of SO2 ≤ 85%, the time to SSC discontinuation due to abnormal SO2 or HR, and episodes of HR < 111 beats per minute (bpm) or > 180 bpm. Subgroups and pooled analysis will be performed to identify if breast-feeding and mother and child positions favor the occurrence of desaturation or bradycardia episodes. Discussion A simple intervention such as modifying mother’s bed angle of inclination while in SSC with her child during the first 2 h postpartum could favor newborn’s hemodynamic and respiratory stabilization and thus contribute to reducing the onset of ALTEs. Trial registration ClinicalTrials.gov, NCT02585492. Registered on 22nd October 2015. Protocol version 2 (30th June 2015).